MRI findings in patients after small-head metal-on-metal total hip arthroplasty with a minimum follow-up of 10 years - Reiner, Tobias; Do, Thuy; Klotz, Matthias C. M.; Hertzsch, Fabian; Gaida, Matthias; Weber, Marc-André; Gotterbarm, Tobias (The journal of bone & joint surgery. A, American volume, 2017)
Concern has been raised about the late onset of adverse reactions to metal debris (ARMD) in patients with a small-head metal-on-metal total hip replacement. The aims of this study were to assess the frequency and characteristic appearance of ARMD in patients with a small-head (28-mm) metal-on-metal total hip replacement and elevated blood ion levels (>1 μg/L) after a minimum follow-up of 10 years and to analyze the possible risk factors associated with the prevalence of these lesions. In the present study, we used metal artifact reduction sequence magnetic resonance imaging (MARS MRI) to investigate the cases of 53 patients (66 hips) with a small-head (28-mm) metal-on-metal total hip replacement and elevated blood ion levels at a mean follow-up interval of 15.5 years (range, 10.6 to 19.3 years). Whole blood metal ion levels (cobalt and chromium), clinical outcome scores (Harris hip score), and radiographs were obtained for each patient. Tissue samples from patients who had revision surgery were histologically examined. MARS MRI revealed ARMD in 27 hips (41%). Most hips with ARMD (67%) were asymptomatic. ARMD were generally small, with a median lesion size of 2.3 cm3 (range, 0.3 to 71.4 cm3) and predominantly cystic in nature. Multivariate regression analysis revealed positive correlation between cobalt ion levels and the presence of ARMD. In this case series, the risk for the development of ARMD was 2.87 times higher for every 1 μg/L increase of blood cobalt ion concentration (95% confidence interval, 1.01 to 8.17; p = 0.048). In this case series, ARMD were seen in 41% of the hips following small-head metal-on-metal total hip arthroplasty at long-term follow-up, and most patients with ARMD were asymptomatic. Blood cobalt ion levels could be identified as a risk factor for ARMD. However, ARMD also occurred in patients with low metal ion levels. Further studies are necessary to investigate the role of ARMD in asymptomatic patients with this bearing type. Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.